Religious identity as the state’s tool in modification of public space and its identity - Hajdinac, Sara (Poligrafi, 2025)
In 1934, after several years of struggle, the Orthodox community of Maribor was awarded a lot to construct a new sacral building on General Maister Square (then Yugoslavia Square) in Maribor, at the site of the recently removed monu-ment dedicated to Vice Admiral Wilhelm Tegetthoff. The square boasts a rich symbolic history, wherein the very names of the square have clearly indicated the identity of the city over time. The new government sought to modify public space in accordance with the new state – these spaces had to be given not only a Slovenian, but also a Yugoslavian identity. The first modification was changing the square’s name to Yugoslavia Square, after which a Serbian Orthodox church was built in the Serbian national architectural style by architect Momir Koruno-vić (1883–1969), who designed all three Serbian sacral buildings in the province of Dravska Banovina (in Maribor, Ljubljana, and Celje). The Church of St. Lazarus was to be ideologically connected to the monument dedicated to King Aleksandar Karađorđević on Liberty Square, which would provide a clear Yugoslavian identity to the city district.
Keywords: art; identiteta; identity; Maribor; Ortodox architecture; politics; politika; pravoslavna arhitektura; umetnost